Pengembangan Sistem Aplikasi untuk Meningkatkan Efisiensi Distribusi Makanan pada Kelompok Masyarakat Sehat Bergizi - Mafrokhah Mafrokhah; Akbar Suseno Tri Maulana; Ihwatun Nupus; Wasis Haryono (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This report is titled "Development of an Application System to Improve the Efficiency of Food Distribution in Nutritious Healthy Community Groups." This research aims to design and implement a technology-based application system that manages the food distribution process for healthy and nutritious community groups, especially for the elderly. The Healthy and Nutritious Community Group is an organization that is committed to providing and distributing nutritious food to the community. One of the main challenges faced by this organization is the lack of efficiency in the distribution process which is still carried out conventionally. This conventional practice often leads to delays in delivery as well as inaccuracies in the distribution of groceries. Data was collected through direct observation and in-depth interviews with the organization's managers as well as the couriers involved in the distribution process.